2019
DOI: 10.1039/c9ra04655k
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the electronic property of hydrogenated 2D tetragonal Ge by applying external strain

Abstract: α- and β-GeH are semiconductors with direct band gap of 0.953 eV and indirect gap of 2.616 eV, respectively. Direct band gap of α-GeH reduces from 2.008 to 0.036 eV as strain increase from −7 to 7%, indirect band gap of β-GeH is changed slightly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The electronic band structures (E-k diagrams) and associated TE properties of SiH and GeH monolayers have been estimated from GGA-PBE level of theory. In this connection it may be relevant to mention that although the PBE functional underestimates the E g values of the crystal systems in general, the same functional however is known to reproduce the similar band dispersion profiles to that of hybrid functionals like HSE as reported elsewhere [3,[50][51][52][53][54][55]. To accomplish a pragmatic balance between the level of theoretical calculations and the computational costs, improved BOMD simulations on the supercell geometries of these systems have been performed with GGA-PBE level of theory to estimate their TE properties under ambient and external strains.…”
Section: Computational Detailsmentioning
confidence: 88%
“…The electronic band structures (E-k diagrams) and associated TE properties of SiH and GeH monolayers have been estimated from GGA-PBE level of theory. In this connection it may be relevant to mention that although the PBE functional underestimates the E g values of the crystal systems in general, the same functional however is known to reproduce the similar band dispersion profiles to that of hybrid functionals like HSE as reported elsewhere [3,[50][51][52][53][54][55]. To accomplish a pragmatic balance between the level of theoretical calculations and the computational costs, improved BOMD simulations on the supercell geometries of these systems have been performed with GGA-PBE level of theory to estimate their TE properties under ambient and external strains.…”
Section: Computational Detailsmentioning
confidence: 88%
“…Subsequently, hydrogenated tetragonal Ge was reported to have two stable configurations, these configurations have a wide band gap which can be further tuned by external strain. 25 The recent study has found that 2D tetragonal silicene is stable and exhibits a nodal line semimetal nature. 14 Additionally, hydrogenation could induce a semimetal–semiconductor transition in 2D tetragonal silicene, this hydrogenated configuration (γ-SiH) is stable.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to T-Graphene, materials with the same tetragonal structure, such as T-Germanene (T-Ge), T-Silicene (T-Si) and T-SiC have been predicted and investigated using DFT calculations 25 , 26 . T-Ge and T-Si are 2D materials composed of a single layer of Ge/Si atoms arranged in a squared lattice structure and they have two Dirac cones in their electronic band structures.…”
Section: Introductionmentioning
confidence: 99%